Acanthosaura phuketensis (Squamata: Agamidae), a new long-horned tree agamid from southwestern Thailand - Pauwels, Olivier S. G.; Sumontha, Montri; Kunya, Kirati; Nitikul, Awat; Samphanthamit, Phamon; Wood, Perry L., Jr.; Grismer, Lee L. (Zootaxa, 2015)
We describe a new lowland forest-dwelling species of the genus Acanthosaura from Phuket Island and the Phuket mountain range in southwestern Thailand. Acanthosaura phuketensis sp. nov., the 11th species in the genus, seems most closely related to A. crucigera from Myanmar and western Thailand and A. cardamomensis from the Cardamom Mountains, but can be differentiated from them by a combination of morphological and coloration characteristics. This new discovery stresses the importance of preserving the last forest patches remaining on Phuket Island, home to three other squamate endemics.